Analisis Hukum Terhadap Peran Penegakan Hukum dalam Mengatasi Peredaran Narkoba - Joy Novi Yanti Lumbantobing; Mima Defliyanti Saragih; Reh Bungana Br PA; Maulana Ibrahim (Hakim, 2023)
Drug trafficking is a serious problem that threatens public health and security. Law enforcement is one of the efforts to overcome drug trafficking. This article aims to analyze the role of law enforcement in dealing with drug trafficking from a legal perspective. The method used in this research is a literature study by collecting data from various trusted sources. The results of the discussion show that law enforcement has an important role in dealing with drug trafficking. However, there are still several obstacles in law enforcement that need to be overcome. The conclusion of this article is that effective and efficient law enforcement can help overcome drug trafficking.